Tabata Training for Increasing Aerobic Capacity. (March 2017) - Imanudin, I; Sultoni, K
Abstract: Futsal is a ball game with speed so that each player is required to have the excellent physical condition. One of the components necessary physical condition of players as the early foundation is endurance (aerobic). There are several training patterns that can be used in improving aerobic capacity. One that has not been widely adopted was the Tabata training. The purpose of this study was to determine whether the application of Tabata training provides a significant effect on aerobic capacity. The method used is the experimental method. The participants in this study was an 18 female student of futsal activity unit of UPI who selected as the team's needs. The sampling technique used the purposive sampling technique. Bleep test was conducted to measure aerobic capacity. The results show that the average of VO2 max score of the pre-test and post-test was 37.7 mL/(kg·min) and 40.5 mL/(kg·min). Thus, there is significant influence Tabata training to increase aerobic capacity.